New Directions for Preventing Dating Violence in Adolescence: The Study of Gender Models - Santoro, Chiara; Martínez-Ferrer, Belén; Monreal Gimeno, Carmen; Musitu, Gonzalo (Frontiers in Psychology, 2018)
Dating violence is a huge transcultural and alarming phenomena, directly linked with endless discrimination against women. The latest research on dating violence in adolescence shows how dating violence is persistent and common in the adolescent period as well and pinpoints the origin of gender violence from first adolescent relationships. This element takes us to considerate how recent gender violence studies and policies, increased also thanks to international efforts on this issue, are not bringing expected results, especially among young people. This Mini-Review aims to analyze the main characteristics of current gender studies and policies on dating violence, focusing on percentages with a woman-centered approach, which stresses the consequences of gender violence. Other gender studies, that consider gender as a relational product, stress the importance of integrating the analysis of gender models as a key instrument to understand the main causes of dating violence, providing new elements to develop effective policies against dating violence. Indeed, gender models of femininity and masculinity are based on a binary system, which is also a reciprocal recognition and identity system: gender models define female and male characteristics, roles, stereotypes, and expectation, being complementary and foreclosing at the same time Recent studies on gender relationships, especially among the youth, allows us to propose a new dialogue between dating violence studies and gender model studies, underling the need of a complete and complex understanding of gender structure, and of its tensions and contradictions, to put an end to gender and dating violence, through effective programs.